Hormonal contraceptive use before hCG remission does not increase the risk of gestational trophoblastic neoplasia following complete hydatidiform mole: a historical database review. (7th October 2015) - Braga, A; Maestá, I; Short, D; Savage, P; Harvey, R; Seckl, MJ
Abstract : Objective: To re‐evaluate the safety of hormonal contraceptives (HC) after uterine evacuation of complete hydatidiform mole (CHM). Design: Historical database review. Setting: Charing Cross Hospital Gestational Trophoblastic Disease Centre, London, United Kingdom. Population: Two thousand four hundred and twenty‐three women with CHM of whom 154 commenced HC while their human chorionic gonadotropin (hCG) was still elevated, followed between 2003 and 2012. Methods: We compared time to hCG remission between HC users and nonusers. The relationship between HC use and gestational trophoblastic neoplasia (GTN) development was assessed. The relationship between HC use and a high International Federation of Gynecology and Obstetrics (FIGO) risk score was determined. Main outcome measures: Time to hCG remission, risk of developing postmolar GTN and proportion of women with high FIGO risk score. Results: No relationship was observed between HC use with mean time to hCG remission (HC users versus non‐users: 12 weeks in both, P = 0.19), GTN development (HC users versus non‐users: 20.1 and 16.7%, P = 0.26) or high‐risk FIGO score (HC users versus nonusers: 0% and 8%, P = 0.15). Moreover, no association between HC and GTN development was found, even when an age‐adjusted model was used (OR = 1.37, 95% CI 0.91–2.08, P = 0.13). Conclusions: The use of current HC is not associated with development of postmolar GTN or delayed time to hCG remission. Therefore, HC can be safely used to prevent a new conception following CHM regardless of hCG level. Tweetable abstract: Non‐concurrent cohort study to re‐evaluate the safety of low dose HCs after uterine evacuation of CHM. Tweetable abstract: Non‐concurrent cohort study to re‐evaluate the safety of low dose HCs after uterine evacuation of CHM.